Carbon monoxide effects on human ventricle action potential assessed by mathematical simulations - Trenor, Beatriz; Cardona, Karen; Saiz, Javier; Rajamani, Sridharan; Belardinelli, Luiz; Giles, Wayne R. (Frontiers in Physiology, 2013)
Carbon monoxide (CO) that is produced in a number of different mammalian tissues is now known to have significant effects on the cardiovascular system. These include: i) vasodilation, ii) changes in heart rate and strength of contractions and iii) modulation of autonomic nervous system input to both the pacemaker and the working myocardium. Excessive CO in the environment is toxic and can initiate or mediate life threatening cardiac rhythm disturbances. Recent reports link these ventricular arrhythmias to an increase in the slowly inactivating, or ‘late’ component of the Na+ current in the mammalian heart. The main goal of this paper is to explore the basis of this pro-arrhythmic capability of CO by incorporating recently reported changes in CO-induced ion channel activity and intracellular signalling pathways in the mammalian heart. To do this, a quite well-documented mathematical model of the action potential and intracellular calcium transient in the human ventricular myocyte has been employed. In silico iterations based on this model provide a useful first step in illustrating the cellular electrophysiological consequences of CO that have been reported from mammalian heart experiments. Specifically, when the Grandi et al. model of the human ventricular action potential is utilized, and after the Na+ and Ca2+ currents in a single myocyte are modified based on the experimental literature, early after-depolarization (EAD) rhythm disturbances appear, and important elements of the underlying causes of these EADs are revealed/illustrated. Our modified mathematical model of the human ventricular action potential also provides a convenient digital platform for designing future experimental work and relating these changes in cellular cardiac electrophysiology to emerging clinical and epidemiological data on CO toxicity.